Direct Distal Renal Artery Aneurysm Repair. (August 2020) - Jayet, Jérémie; Davaine, Jean-Michel; Tresson, Philippe; Verscheure, Dorian; Lawton, James; Kashi, Mahine; Couture, Thibault; Gaudric, Julien; Chiche, Laurent; Koskas, Fabien
Abstract : Objective: Treatment of renal artery aneurysms (RAA) remains controversial. Endovascular treatment has increased for main trunk and for very distal aneurysms, whereas for lesions located at the bifurcation surgical treatment seems to be a valid option. The goal of this study was to describe the technique of direct reconstruction of RAA and to report on outcomes. Methods: This study comprised single centre prospective collection of data with retrospective analysis (January 2015 to August 2018) of patients operated on for distal RAA using direct reconstruction. Results: A total of 24 RAA in 21 patients (seven men and 14 women, mean age 59 ± 13 years) was included. History of hypertension was found in 15 patients and renal insufficiency was present in one. Mean pre-operative systolic and diastolic blood pressures were 134 ± 21 mmHg and 74 ± 10 mmHg, and mean pre-operative rates of creatinine and glomerular filtration rate were 67 ± 13 μmol/L and 93 ± 49 mL/min/1.73 m 2, respectively. Indications for repair were a diameter >20 mm in seven cases (mean diameter = 25 ± 2 mm) or rapid growth in one case, symptomatic aneurysm in 12 cases (hypertension, haematuria, pain), and a concomitant lesion in four cases (splenic aneurysm, abdominal aortic aneurysm, occlusive visceral artery lesions). All lesions were distal, main artery bifurcation in 22 cases and hilar in two cases. The main aetiology was fibromuscular dysplasia (16 cases) followed by atherosclerosis (seven cases) and one case of Ehlers Danlos Syndrome. In situ reconstruction was possible for 22 RAA, while two cases required kidney autotransplantation. The mean renal ischaemia time was 18 ± 5 min. At two years, the patency rate was 100%, and mean systolic blood pressure decreased (134 mmHg–122 mmHg, p = .047). Renal function was stable from 93 ± 49 pre-operatively to 95 ± 35 mL/min/1.73 m 2 in the post-operative course ( p = .56). Conclusion: Direct reconstruction appears to be efficient for most RAA. This technique is complementary to ex vivo autotransplantation and endovascular treatment.